The true Israel : uses of the names Jew, Hebrew, and Israel in ancient Jewish and early Christian literature - Harvey, Graham, 1959- (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1996)
Many studies have portrayed Judaism in Antiquity as sectarian, with a variety of groups all claiming to be The True Israel. Early Christianity is alleged to have begun in this context as one more Jewish sect claiming such authority. However, the second-century Christian Justin Martyr is the first person known to have used the phrase 'the True Israel'. This book examines the uses of the names 'Jew', 'Hebrew' and 'Israel' in the surviving literature - especially the Bible, Dead Sea Scrolls, Philo, Josephus, New Testament and Mishnah - to determine whether this is an adequate or accurate picture. It discusses the associations of each word, as determined by their actual usage and collocations rather than their theoretical origins. It will be of value to scholars of ancient Judaism and early Christianity. This publication has also been published in paperback, please click here for details.